Barack Obama : president for change - Hicks, Peter, 1952- (New York : Powerkids Press, 2013)
A brief biography of President Barack Obama, describing his childhood and education, and discussing things that have inspired his life and work, his professional accomplishments, and his contributions to the world. Includes a quiz.
Includes bibliographical references (p. 31) and index.
3-6
Keywords: Obama, Barack -- Juvenile literature; Obama, Barack; Obama, Barack; Presidents -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Presidents; African Americans -- Biography; Presidents -- United States -- Biography